Representation Of Urban Lifestyle in The Form of a Large Electric Scooter Design - Akmal Fadhlurrahman SANTOSO; Narhendrha Putra Sardjana (Texture : Art And Culture Journal, 2025)
This research explores electric scooters in urban environments in Indonesia, with a focus on adapting technology and design to dense urban conditions. Electric scooters offer eco-friendly mobility solutions amid challenges such as congestion and diverse road infrastructure. Through qualitative research methods, this study assesses the preferences of urban users towards the dimensions, features, and design of electric scooters. The results of the interviews show that scooters with large dimensions, features such as delivery boxes, and efficient lights are highly desirable for comfort and safety in cities. Modern casual designs are also preferred because they are practical for everyday use. This research highlights the need for further development to create a more e-scooter-friendly urban environment, as well as the importance of design that is responsive to the needs of urban users.